Relevansi Asbabun Nuzul Ayat-Ayat Jihad dalam Menangkal Paham Terorisme di Era Digital - Anugrah; Nasrullah Bin Sapa; Muhammad Amin Sahib (Yayasan Al-Afif, 2025)
This study aims to examine the relevance of the asbābun nuzūl (occasions of revelation) of jihad-related verses in efforts to counter radicalism and terrorism in the digital era. Advances in information technology and social media enable information to spread rapidly and widely, including literal interpretations of jihad verses that are often misused by extremist groups as a justification for violence against anyone they consider an enemy. This research employs a descriptive qualitative method with a library research approach and contextual–historical content analysis techniques to comprehensively understand the context in which the verses were revealed. The findings show that understanding asbābun nuzūl allows society to interpret jihad verses according to their historical and Shar‘i context, distinguishing between defensive jihad or the enforcement of justice and aggressive violence. The analysis of jihad verses, such as Q.S. Al-Baqarah [2]: 218 and Q.S. At-Tawbah [9]: 29, emphasizes that these verses were revealed within the context of self-defense and community protection, not as a justification for terrorism. Thus, asbābun nuzūl becomes an important instrument for intellectually safeguarding society, critically evaluating religious narratives, and preventing the spread of extremist ideologies in cyberspace.